Paper Soap Formulation with The Addition of Seaweed Gracillaria sp. as an antibacterial and antioxidant - Tri Widayati Putri; Riskawati Riskawati; Jawiana Saokani Sofyan (Indonesian Journal of Coastal and Marine Studies, 2025)
This study aims to find out the best formulation of paper soap with the addition of seaweed Gracilaria sp. in paper soap preparations against antibacterial, antioxidant and pH values. Seaweed sample Gracilaria sp. taken in Takalar district, sampling was carried out by Complete Random Design (RAL) with a simple random sampling technique. Data analysis was used descriptive on antibacterial and antioxidant tests and ANOVA on pH tests. The results showed that the highest or strongest antibacterial inhibition zone value in paper soap was found in the sample concentration of 30% with an average of 14.20, at a concentration of 20% with an average of 10.80 classified as strong and a concentration of 0% with an average of 7.15 classified as moderate. Meanwhile, the average value of antioxidant activity at a concentration of 0% of 23.727 ppm is relatively strong, at 20% concentration of 28.87 ppm is classified as strong and the concentration of 30% at 31.528 ppm is classified as high and strong. for the average value in the pH test at a concentration of 0% of 10.20, a concentration of 30% of 10.26 and the highest is a concentration of 20% with an average magnitude of 10.38. The conclusion of the results of the variety analysis showed that the formulation of paper soap preparations increased the addition of seaweed Gracilaria sp. then the better the antibacterial and antioxidant value, but the pH test is still less effective and still requires the addition of vitamins to lower the pH value a little.